Effects of three different stretching protocols on hamstring muscle flexibility in professional soccer players: a randomized study - Manzi, V.; Iellamo, F.; Alashram, A. R.; D'onofrio, R.; Padua, E.; Casasco, M.; Annino, G. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The current study aimed to investigate and compare the influences of global postural rieducation techniques (GPR), stretching exercises on a whole-body vibration platform (WBV), and static stretching exercises on hamstrings flexibility in elite soccer players. METHODS: 24 professional soccer players were randomly assigned to either global postural re-education (N.=8), stretching on whole-body vibration group (N.=8) or static stretching (N.=8), during the first 4 weeks of the precompetitive season. Assessment of hamstring muscle flexibility was performed using a straight leg raise test. All participants were assessed three times: at baseline, at the end of the study protocol and 14 days after the end of the study protocol. RESULTS: The short-term increase in hamstring muscle flexibility was observed in all 3 groups, without significant differences among groups. However, after 14 days from the end of the interventions only the WBV group maintained the flexibility level achieved just at the end of the protocol with no significant changes in both legs whereas a significant decrease in the SLRT in GPR and SS groups, in right and left legs (GPR, P=0.002; P=0.015; SS, P=0.0001; P=0.0001), was observed. CONCLUSIONS: These results would suggest that GPR, static stretching on whole-body vibration and static stretching techniques all improve hamstring muscle flexibility, but only stretching on WBV maintains the effect over time in professional soccer players.